Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376421
|View full text |Cite
|
Sign up to set email alerts
|

FoodFab: Creating Food Perception Illusions using Food 3D Printing

Abstract: Food 3D printing enables the creation of customized food structures based on a person's individual needs. In this paper, we explore the use of food 3D printing to create perceptual illusions for controlling the level of perceived satiety given a defined amount of calories. We present FoodFab, a system that allows users to control their food intake through modifying a food's internal structure via two 3D printing parameters: infill pattern and infill density. In two experiments with a total of 30 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 57 publications
0
25
0
1
Order By: Relevance
“…Rather than digitally augmenting food, we showed how to use food 3D printing to physically integrate perceptual illusions. For more details regarding the user studies and computational models, please refer to [1].…”
Section: Resultsmentioning
confidence: 99%
“…Rather than digitally augmenting food, we showed how to use food 3D printing to physically integrate perceptual illusions. For more details regarding the user studies and computational models, please refer to [1].…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple examples of multisensory experiences in the context of MHFI that can further help to illustrate what they mean in HFI. Situated on the real end of the reality-virtuality continuum, FoodFab capitalizes on 3D printing to control parameters of the internal structure of foods (infill pattern and infill density) and, thus, influence chewing time and, in turn, satiety (Lin et al, 2020). In mixed reality, an example is MetaCookie, a system that augments a cookie's flavor by digitally overlapping colors and textures, as well as specific aromas, on a plain cookie (Narumi et al, 2011).…”
Section: Where Food Meets Multisensory Technologymentioning
confidence: 99%
“…In addition, researchers found that using different infill patterns affect the infill densities and size of the printed food [63]. In cookie samples, lower infill densities required fewer ingredients and hence bigger sizes, whereas the cookies with the largest infill had the smallest size.…”
Section: Limitationsmentioning
confidence: 99%
“…All the cookies included the same amount of ingredients and hence the same amount of calories. However, the bigger the cookies, the more time was required for the panel participants to chew and the more satiety that they perceived [63]. Therefore, playing with the 3D printing shape and patterns can help tackle obesity.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation